Coronary angiographic profile in patients with failed thrombolysis - Saravanan M; Vinodkumar Balakrishnan; Muralidharan TR (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2019)
Background: Acute Myocardial Infarction (MI) is a life threatening condition responsible for over 85% of the deaths all over the world. The management of MI has to be done on an emergency footing, without losing any time. The standard protocol involves thrombolysis in these patients. However, not all the thrombolysis procedures turn out to be successful. This study was done to explore the prevalence and risk factors associated with the success of thrombolysis.